PERBANDINGAN PUISI DIA DAN AKU KARYA SITUR SIMORANG DENGAN LOVE’S PHILOSHOPY KARYA PERCY BYSSHE SHELLEY - Nathasya, Rindi; Saputry, Dessy; Ridayani, Ridayani; Khoirotun Nisa, Amida (Pascasarjana, Universitas Negeri Gorontalo, 2023)
This research describes the comparison of Dia and Aku by Sitor Situmorang and Loves's Philosophy by Percy Bysshe Shelly. This research uses a qualitative description method. This method is used to explain the overall results of the analysis that has been carried out in the form of words or verbal expressions of what has been observed. The results of this research are the similarities and differences in the poems Dia and Aku by Sitor Situmorang and Love's Philosophy by Percy Brsshe Shelley. These similarities can be seen from the writing style, title, meaning, theme that tells the story of a relationship. The poem Love's Philosophy by Percy Bysshe Shelley raises the theme of love, because love and relationships should be the most important things in a person's life. However, this poem depicts the opposite, namely unrequited love or what is usually called unrequited love because there is an element of rejection.